Brief report: A growth mixture model of occupational aspirations of individuals with high‐incidence disabilities. Issue 1 (5th December 2012) - Lee, In Heok; Rojewski, Jay W.
ABSTRACT: A previous longitudinal study of the occupational aspirations of individuals with high‐incidence disabilities revealed multiple longitudinal patterns for individuals with learning disabilities or emotional–behavioral disorders. Growth mixture modeling was used to determine whether individuals in these two high‐incidence disabilities groups ( N  = 585) possessed heterogeneous aspirations trajectories. Two distinct classes emerged. Among selected covariates (inc., gender, SES, locus of control, self‐concept, mathematics achievement), only gender and SES significantly distinguished group membership. While no covariates were significantly related to the growth factors for latent class 2 (low aspirations), math achievement and SES were significantly related to initial aspirations in latent class 1 (high aspirations). Moreover, for latent class 1, the occupational aspirations of individuals with learning disabilities became increasingly lower than adolescents with emotional‐behavior disorders after high school. Possible explanations for this phenomenon are considered.